Advancements in the Treatment of Diabetic Macular Edema: Current Strategies and Future Directions - Czach, Zuzanna; Czach, Magdalena; Bachurska, Dominika; Kopacz, Wojciech; Mazurek, Łukasz; Stradczuk , Monika; Mazurek, Wojciech; Rękas, Barbara; Kruczyk, Barbara; Piętak, Mateusz; Olędzka, Joanna (Journal of Education, Health and Sport, 2024)
This narrative review examines current and emerging treatment strategies for diabetic macular edema (DME), a complication of diabetic retinopathy characterised by fluid accumulation in the macula, which can lead to vision impairment. The incidence of DME is particularly high in patients with long-standing diabetes and advanced retinopathy. The current treatment options for DME include anti-vascular endothelial growth factor (anti-VEGF) agents, corticosteroids, and laser therapies. Anti-VEGF agents, including bevacizumab, ranibizumab, aflibercept, and the more recently developed brolucizumab and faricimab, have been demonstrated to reduce macular thickness and improve visual acuity. Brolucizumab offers the advantage of fewer injections due to its longer duration of action, although it carries a higher risk of ocular inflammation compared to other anti-VEGF agents. The dual inhibition of the VEGF and angiopoietin-2 (Ang-2) pathways by faricimab may enhance vascular stability and reduce inflammation, potentially improving patient outcomes. Steroid therapies, including dexamethasone, fluocinolone acetonide, and triamcinolone acetonide, represent an alternative for patients who do not respond adequately to anti-VEGF treatment. Laser therapies, including focal, navigated, and subthreshold laser treatments, remain a crucial component in the management of DME, with the ability to seal leaking vessels and reduce fluid accumulation. In order to achieve the best outcomes for patients, it is essential to continue to advance these treatment modalities and adopt a personalised, multifaceted approach.